A reusable ratiometric two-photon chemodosimeter for Hg2+ detection based on ESIPT and its application in bioimaging1. Issue 17 (7th May 2015) - Luo, Weifang; Jiang, Huie; Zhang, Kaiming; Liu, Wei; Tang, Xiaoliang; Dou, Wei; Ju, Zhenghua; Li, Zhiqi; Liu, Weisheng
<x xml:space="preserve">Abstract</x> A novel reaction-based recyclable two-photon chemodosimeter for Hg2+ detection in nearly aqueous solution was developed, which could be used for bioimaging.